Using of seaweed extract in diets of japanese quails: 2. the effects of seaweed extract on egg yield - Fatma İnal; Behiç Coşkun; M. Kemal Çiftçi; Nurettin Gülşen (Eurasian Journal of Veterinary Sciences)
Two trials were conducted in this study. In the flrst trial, total 72 female Japanese quails aged 5 weeks were used. During 8 weeks. the animals fed diets contalnlng 0, 0.01, 0. 1 and 1 % Maxicrop extracted from Ascophyllum nodosum. The effects of Maxicrop on egg productıon. egg weight, feed lntake, feed effıciency, body weight and egg yolk color ın quails were investigated. In the second trial, total 20 Japanase quaııs (8 males+ 12 females) at the age of 8 weeks were u sed. Maxicrop was added to basaı dlet at the levels of 0. 1, 2 and 4 %, and whether ıts toxic etfects were determıned.The results of this study were summarised as follows. 1. No positive effect of seaweed extract on egg productlon, egg weight. feed efficiency and body weıght was determıned 2 Seaweed extracı atfected positively to yolk color. 3. Seaweed extract may use in the dıets of laying quails up to 4 % without deleterious effects.